An Empirical Analysis on the Determinants of Foreign Subsidiary’s Local Embeddedness: Focusing on Korean MNCs in China - KIM, Byoung-Goo; KIM, Gyu-Bae (The Journal of Asian finance, economics, and business, 2020)
The purpose of this paper is to empirically analyze the determinants of foreign subsidiary’s local embeddedness because it is critically important for the subsidiary to build a variegated local network. This paper suggests that a MNC’s global capability, the degree of autonomy granted by the headquarters of the multinational corporation to its foreign subsidiary, the foreign subsidiary’s absorptive capacity based on local environment, and its level of localization will affect the subsidiary’s local network embeddedness. The empirical analysis confirmed that when the headquarters gives the foreign subsidiary more autonomy, this has a positive effect on the local embeddedness of the foreign subsidiary and when the foreign subsidiary has a strong absorptive capacity, this has a positive correlation with the local embeddedness of the foreign subsidiary. And this paper found that when the foreign subsidiary has achieved a high level of staff localization, this foreign subsidiary will have a higher level of local embeddedness. This study identified the preceding conditions necessary for a foreign subsidiary of a multinational corporation to effectively embed itself in the local network by analyzing factors related to the multinational corporation’s headquarters and subsidiaries, and thus contributes significantly to continued research on the local embeddedness of subsidiaries.